Payments to the National Rehabilitation Fund for People with Disabilities as a Stimulant to Employ People with Disabilities during the COVID-19 Pandemic - Koza, Andrzej; Politaj, Adriana (Wpłaty na Państwowy Fundusz Rehabilitacji Osób Niepełnosprawnych jako stymulanta zatrudnienia osób z niepełnosprawnością w dobie pandemii COVID-19, 2023)
The aim of the study is to determine the changes in the employment of people with disabilities during the pandemic and the effectiveness of the system of financial penalties for employers in the event of failure to comply with the statutory obligations to employ people with disabilities as incentives to employ such people. The time range of the research was set for the years 2017-2021 and the first half of 2022. The following research methods of a general nature were used in the article: the method of analysis and criticism of source literature, the inductive and deductive method, as well as analysis and synthesis. In addition, detailed methods were also used: descriptive, monographic and document research. Research hypothesis: financial penalties imposed on employers for not employing the percentage of disabled people required by law were more effective in stimulating employers to improve the employment rate of people with disabilities during the COVID-19 pandemic than before its outbreak. In the light of the conducted research and literature studies, the effectiveness of penalties as a stimulant to employ people with disabilities in particularly difficult macroeconomic conditions was noticed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 2, s. 49-59
Keywords: people with disabilities; employment; quota system; osoby z niepełnosprawnością; zatrudnienie; system kwotowy